Efektivitas Penerapan Media AI Presenter D-ID Dalam Meningkatkan Maharah Istima’ Siswa Ma Hasyim Asy’ari Jogoroto Jombang - Bachrudin, Muhammad Ali; Rizki, Restu Budiansyah (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2025)
In the current digital era, Arabic language teaching must evolve in line with advances in science and technology. In the field of education, the presence of AI offers significant potential to enhance the quality and effectiveness of learning, including in the cultivation of Maharah istima’ (listening skills). A primary challenge encountered by students encompasses both linguistic and non-linguistic factors, such as restricted vocabulary, difficulty in identifying phonetic sounds, issues with pronunciation and writing, a deficiency in concentration, and the insufficiency of suitable learning media. AI Presenter D-ID presents a potential solution to these problems. This study examines the effectiveness of AI Presenter D-ID in improving listening skills among tenth-grade students at MA Hasyim Asy'ari Jogoroto Jombang, using a quantitative approach with a one-group pretest-posttest pre-experimental design. The subjects of this study were all 27 students of class X-3 at MA Hasyim Asy’ari Jogoroto Jombang. Because the population size was under 100, the entire population was utilized as the research sample without the implementation of sampling techniques. Data were gathered through tests and documentation. The findings of the study demonstrate a significant enhancement in students' Maharah istima’ following the treatment. Based on the Wilcoxon Signed Rank Test, the result showed an Asymp. Sig. (2-tailed) value of 0.041<0.05. Consequently, the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. This leads to the conclusion that the use of AI Presenter D-ID is effective in improving the Maharah istima’ of students in class X-3 at MA Hasyim Asy’ari Jogoroto Jombang. Keywords: Learning Media, AI Present er D-ID, Maharah Istima’.